Escalation of Suicidal Spectrum Behaviors During Incarceration. (May 2023) - Yasmeen, Sajida; Stuewig, Jeffrey B.; Wilson, John S.; Tangney, June P.; Schrader, Shannon W.; Loya, Jennifer M.; Barboza, Sharen E.; Berry, Diane; Wiser, Abigail
Rates of multiple episodes of suicide spectrum behaviors are higher among incarcerated individuals than community members. Understanding the trajectory of multiple episodes of suicide spectrum behavior is important for assessment of risk and precautionary measures. We examined escalation in terms of frequency and method among 204 incarcerated individuals who engaged in multiple episodes of serious self-harm. Among those who did not die ( n = 191), the interval between suicide spectrum behaviors decreased across incidents and incidents became potentially more lethal over time. Findings indicate that clinicians relying solely on intent to assess seriousness of self-harming behavior might overlook escalation risk. To effectively prevent fatal incidents, clinicians and correctional staff working with incarcerated individuals should incorporate behavioral measures (e.g., time between incidents and method used) and trend these measures over time.